Time courses for pulmonary oxygen uptake and cardiovascular responses are similar during apnea in resting humans - Andersson, Johan P. A.; Bacanovic, Tim; Chen, Philip; Lodin-Sundström, Angelica; Halder, Amitava; Persson, Gustav; Linér, Mats H.; Sjögreen, Bodil (Frontiers in Physiology, 2025)
IntroductionThe pulmonary oxygen uptake is reduced during apnea, compared to eupneic baseline, preserving the pulmonary oxygen store. This study elucidates the time course for this reduction, comparing it to the time course for apnea-induced cardiovascular responses.Methods and resultsExperiments involved two groups, performing apneas during rest, both without and with cold-water face immersion (A and AFI). The first group (n = 18) performed A and AFI of gradually increasing durations (from 15 to 120 s, order unknown to participant), allowing analysis of the time course for apneic pulmonary gas exchange. The second group (n = 18) performed A and AFI of identical durations (mean: 137 s), allowing analysis of cardiovascular and respiratory responses. The time course for pulmonary oxygen uptake was similar to the time courses for heart rate and cardiac output, i.e., following a brief increase from eupneic baseline during the initial 15 s of A and AFI, the oxygen uptake was gradually reduced during apnea, reaching a sub-eupneic level from 30 s of apnea and onwards. Changes were augmented during AFI compared to A. Observations confirmed that cardiovascular responses to apnea, including a reduced cardiac output, reduced peripheral blood flow, and most likely a peripheralization of blood volume, preserved the pulmonary oxygen store, while the peripheral venous oxygen stores were depleted to a greater extent.ConclusionsWe conclude that the central, pulmonary oxygen store is preserved with augmented cardiovascular responses to apnea, at the expense of peripheral venous oxygen stores, with a time course similar to that of the cardiovascular responses.